(untitled) (Research, Society and Development, 2020)
The present work aimed to evaluate the dry mass yield and nutritive value of elephant grass cultivars during the dry season (under irrigation) and water. The experiment was carried out at IF Goiano - Campus Ceres in a randomized block design in split plots with 4 replications. The treatments corresponded to the cultivars of Cameroon Common elephant grass, Cameroon Roxo, BRS Capiaçu, BRS Canará, BRS Kurumi and Napier and three regrowth periods (45, 60 and 75 days). Leaf: stem ratio (F: C), green forrage yield (GFY) and dry mass yield (DMY), acid detergent fiber (ADF) and neutral fiber (NDF) and crude protein (CP) were evaluated. The cultivar Napier presented lower NDF in the water season, higher GFY at 75 days and higher DMY, along with BRS Capiaçu in the dry season while Cameron presented the highest DMY in the waters. CP did not differ between treatments. BRS Kurumi has higher F:C ratio and higher bromatological quality indicated by higher CP, lower ADF and NDF. Increasing the cutting age reduces the quality of the cultivars, being in smaller magnitude for the cultivar BRS Kurumi. Irrigation during the dry season maintains the nutritional quality of elephant grass.